The content of iodine in pork - I. Herzig; J. Travnicek; J. Kursa; V. Kroupova (Veterinární Medicína, 2005)
The present study brings current information on providing market pigs and sows with the required iodine level up to date. The results were obtained by the determination of the iodine content in leg muscles and by the relationship between those concentrations and the iodine intake by the human population. The iodine content was assessed by the Sandell-Kolthoff method in 108 samples of leg muscles (m. gracilis) of market pigs from 18 herds in 10 districts of the Czech Republic collected during the period April 2004 to August 2004. Average iodine content in leg muscles of market pigs was 25.6 ± 15.54 μg I/kg fresh matter, median 20.2 and coefficient of variation 60.6%. Significantly higher (P < 0.05 to P < 0.001) iodine levels were recorded in the leg muscles was of herds LI2, ZU, BR, FU, BU, ST and some others. Iodine level variations in the samples from respective farms were expressed in the levels range of 8.5 to 66.2 μg I/kg. The detected variations might have been caused by different iodine saturation of the pigs from different herds, their physiological requirement, manifestation of physiological ability of respective animals to utilize the iodine source, potential effect of goitrogens and environmental conditions. It is necessary to consider the iodine content in pork in the balance of the iodine supply in the shopping basket of consumers. Provided that the average annual consumption of pork is 40.9 kg with iodine content of 25.6 μg/kg(8.5 to 66.2 μg/kg), the average annual iodine intake is 1047 μg, which represents 1.4 to 2.4% of the required intake per person per year.